Bentuk Kekerasan Pada Sinetron Anak Langit - Jubaidah Berthniastuti Matau; M. Abdul Ghofur (Unitri Press, 2019)
Anak Langit soap opera is a soap opera broadcast by sctv stations produced by sinemart. The program is very popular with the audience, especially among teenagers who are still sitting on the school bench. This soap opera shows many events that are not educational to the audience such as scenes of violent acts in the form of brawls, reckless wild races on the highway and scenes of love outside the boundaries as school children. The focus of the problem that will be examined is the meaning of icons, indexes and symbols, and also forms of violence in the soap opera shows. In this study using qualitative research methods by collecting data through observation, interviews and documentation.The results of this study can be concluded that every scene that is in the soap opera child sky has a meaning that affects the assumptions for the community because not only adults who watch this program, but also many children who watch the show moreover this soap opera airing on primetime. These things tarnished the meaning of love in the soap opera anak langit.